Maria Hupfield: Reimagining Research & Roots - Hupfield, Maria; DeMarco, Carla (Office of the Vice Principal, Research, University of Toronto Mississauga, 2019)
This is an audio recording from the podcast series "View to the U: An eye on UTM research". Maria Hupfield is an Assistant Professor cross appointed in the Departments of Visual Studies and English & Drama at UTM. She is UTM’s first Canada Research Chair in Transdisciplinary Indigenous Arts, she is a globally renowned Indigenous performance artist, coming to UTM hot off the heels of nearly a decade based in Brooklyn, New York, making her mark in art circles there, and she also happens to be returning to her alma mater where she completed her own studies in Art and Art History at UTM in 1999. Over the course of this interview on VIEW to the U Maria talks about the power and impact of art, some of the projects she will be undertaking as part of her Canada Research Chair (CRC) designation, how her innovative industrial-felt creations have pioneered a closer connection between craft and art, and how youth have the potential to reinvigorate ideas and perspectives. Prior to coming to UTM, Maria was based in the U.S., where she co-founded Native Art Department International with Jason Lujan. She was an Assistant Professor in Visual Art and Material Practice in the Faculty of Culture and Community at Emily Carr University of Art and Design from 2007-11, and her art exhibitions have been seen throughout Canada and the United States, as well as Venice, Zurich, and Paris. Her areas of expertise include performance practice that references Anishinaabeg oral history and feminist-performance history, Native Feminisms, and she works in a variety of media including sculpture, video and performance.